Tuberculosis Preventive Treatment in People Living with HIV in Uganda: Facilitators and Barriers for Initiation and Completion - Mande, Ritah; Thekkur, Pruthu; Mudoola, Denis; Nsonga, Joseph; Dongo, John Paul; Muchuro, Simon; Turyahabwe, Stavia; Luzze, Henry; Namuwenge, Proscovia; Dar Berger, Selma; Lukoye, Deus; Charles, Macarthur; et al. (Tropical medicine and infectious disease, 2025)
Tuberculosis preventive treatment (TPT) is a mainstay for reducing the tuberculosis (TB) burden among people living with human immunodeficiency virus (PLHIV). Context-specific challenges hinder TPT uptake and completion among PLHIV. During 2022–2024, a mixed-methods design was used to evaluate the TPT cascade and explore its facilitators and barriers among PLHIV availing care from 12 PEPFAR-supported health facilities in Uganda. The quantitative component included analysis of routine programmatic data, and the qualitative component included focus group discussions and in-depth interviews with healthcare workers and PLHIV. A total of 1349 PLHIV were enrolled in the evaluation. Among PLHIV newly initiated on ART (≤3 months), 74% started TPT, and 98% of them completed it. In PLHIV already on ART, 87% had initiated TPT (76% before and 11% during this evaluation), with a treatment completion rate of 98%. The facilitators for TPT implementation included access to shorter TPT regimens, integration of services, and adherence counseling. Barriers included knowledge gaps, pill burden, TPT drug stock-outs, and documentation inconsistencies. The TPT completion rate was higher than the national target (90%), but the TPT initiation remains low. Improved access to shorter regimens, adherence counseling, better documentation, and service integration can sustain the completion rate and improve the initiation rate in Uganda and possibly elsewhere.